LEGAL BASIS OF POLITICAL PARTIES AND ITS OWN CHARACTERISTICS (Scientific journal of the Fergana State University, 2024)
This article presents ideas about the role and importance of political parties as a certain part of a non-profit organization. Political parties play an important role in democratic countries. They express the political will of various classes and groups of the population and play an important role in ensuring the participation of citizens in the management of the state and society.